Tinjauan Hukum Keabsahan Tanda Tangan Elektronik dalam Akta Notaris Berdasarkan Konsep Cyber Notary (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The concept of cyber notary introduces Notaries to utilize information technology and the internet in carrying out their duties and authority. However, there is currently no clear regulation regarding this matter. This research aims to determine the validity and evidential strength of notarial deeds signed using electronic signatures. The research employs a socio-legal empirical method with descriptive analytical specifications, further analyzed qualitatively. Both primary and secondary data will be utilized, referring to relevant laws and regulations concerning the researched issue. The research findings indicate that notarial deeds signed with electronic signatures are declared invalid due to non-compliance with laws and regulations. Similarly, their evidential strength is degraded from authentic deeds to private deeds. The consequence of this degradation is weakened and imperfect evidential strength. The establishment of new legislation is required to support the UUJN (Notary Law) governing cyber notaries, ensuring legal certainty in notarial deeds signed with electronic signatures.this act it is categorized as piracy which violates the provisions in Article 113 paragraph (4).